Fetal microglial phenotype in vitro carries memory of prior in vivo exposure to inflammation - Cao, Mingju; Cortes, Marina; Moore, Craig S.; Leong, Sooyuen; Durosier, Lucien D.; Burns, Patrick; Fecteau, Gilles; Desrochers, Andre; Auer, Roland N.; Barreiro, Luis; Antel, Jack; Frasch, Martin G. (Frontiers in Cellular Neuroscience, 2015)
Objective. Neuroinflammation in utero may result in life-long neurological disabilities. The molecular mechanisms whereby microglia contribute to this response remain incompletely understood. Methods. Lipopolysaccharide (LPS) or saline were administered intravenously to non-anesthetized chronically instrumented near-term fetal sheep to model fetal inflammation in vivo. Microglia were then isolated from in vivo LPS and saline (naïve) exposed animals. To mimic the second hit of neuroinflammation, these microglia were then re-exposed to LPS in vitro. Cytokine responses were measured in vivo and subsequently in vitro in the primary microglia cultures derived from these animals. We sequenced the whole transcriptome of naïve and second hit microglia and profiled their genetic expression to define molecular pathways disrupted during neuroinflammation. Results. In vivo LPS exposure resulted in IL-6 increase in fetal plasma 3 h post LPS exposure. Even though not histologically apparent, microglia acquired a pro-inflammatory phenotype in vivo that was sustained and amplified in vitro upon second hit LPS exposure as measured by IL-1β response in vitro and RNAseq analyses. While NFKB and Jak-Stat inflammatory pathways were up regulated in naïve microglia, heme oxygenase 1 (HMOX1) and Fructose-1,6-bisphosphatase (FBP) genes were uniquely differentially expressed in the second hit microglia. Microglial calreticulin/LRP genes implicated in microglia-neuronal communication relevant for the neuronal development were up regulated in second hit microglia. Discussion. We identified a unique HMOX1down and FBPup phenotype of microglia exposed to the double-hit suggesting interplay of inflammatory and metabolic pathways as a memory of prior inflammatory insult. These findings suggest new therapeutic targets for early postnatal intervention to prevent brain injury.